Environmentalism unbound : exploring new pathways for change - Gottlieb, Robert (Cambridge, Mass. ; London : MIT Press, 2002)
In Environmentalism Unbound, Robert Gottlieb proposes a new strategy for social and environmental change that involves reframing and linking the movements for environmental justice and pollution prevention. According to Gottlieb, the environmental movement's narrow conception of environment has isolated it from vital issues of everyday life, such as workplace safety, healthy communities, and food security, that are often viewed separately as industrial, community, or agricultural concerns. This fragmented approach prevents an awareness of how these issues are also environmental issues.After tracing a history of environmental perspectives on land and resources, city and countryside, and work and industry, Gottlieb focuses on three compelling examples of this new approach to social and environmental change. The first involves a small industry (dry cleaning) and the debate over pollution prevention approaches; the second involves a set of products (janitorial cleaning supplies) that may be hazardous to workers; and the third explores the obstacles and opportunities presented by community or regional approaches to food supply in the face of an increasingly globalized food system.
ENG
Keywords: Environmentalism -- United States; Environmental justice -- United States; Pollution prevention -- United States